Space and the Papacy - Guy Consolmagno (Religions, 2020)
There has always been a powerful connection in human consciousness between the beauty and otherworldliness of the night sky, and humanity’s religious yearnings toward a reality beyond the mundane. When Pope Leo XIII established an astronomical observatory in 1891, it was as a way of demonstrating the Church’s support of science; his choice of astronomy in particular was based primarily on the Holy See’s already established good reputation in the field, and specific opportunities for international collaborations. Nonetheless, since its founding, Popes have taken advantage of the natural connection between sky and “heaven” to promote the exploration of space as a way of coming closer, emotionally and intellectually, to the Creator. However, the nature of how this connection is understood has changed significantly over the past 125 years, most recently with the challenges of the Space Age.